Variations in the Flow Rate of Activated Carbon Filtration are implemented to reduce the amount of biochemical oxygen demand in a Gray Water Canteen - Nadiyah, Milania; Yulianto, Bambang; Ardiani S., Yosephina (Poltekkes Kemenkes Banjarmasin Jurusan Kesehatan Lingkungan Banjarbaru, 2023)
Domestic liquid waste stemming from cooking and cleaning activities poses a significant environmental concern. Initial tests revealed a high Biochemical Oxygen Demand (BOD) level of 376 mg/L, far exceeding the permissible limit of 30 mg/L, according to Ministry of Environment and Forestry Regulation No. 68 of 2016. Failure to treat this waste could have detrimental effects on the environment. This study aims to evaluate the efficacy of varying flow rates in reducing BOD levels in canteen liquid waste, employing activated carbon derived from coconut shells. Employing an experimental design without control, the research encompassed three flow rate treatments: 1.2, 1.3, and 1.4 liters per minute, each repeated six times. Thirty-six samples, equivalent to 54 liters of waste, were analyzed, exhibiting a normal data distribution. Results indicated a notable reduction in BOD levels across all flow rate variations. Specifically, the average decrease was 109.68 mg/L, 107.57 mg/L, and 99.52 mg/L for flow rates of 1.2, 1.3, and 1.4 liters per minute, respectively. These findings underscore the effectiveness of varying flow rates in mitigating BOD in domestic liquid waste. Further research includes investigating activated carbon media's saturation point to optimize its adsorption capacity and determining reactivation timelines. Such endeavors are crucial for refining waste treatment processes and minimizing environmental impacts.